Influence Of Earning Per Share (Eps) And Price Earning Ratio (Per) On Stock Prices On Food And Beverages Companies Listed On The Indonesia Stock Exchange In 2015-2019 - Zaenuddin Haji (DESANTA (Indonesian of Interdisciplinary Journal), 2020)
The Price of Share effect by Earning Per Share (EPS) and Price Earning Ratio (PER). Earning per share is reflection of performance and business of corporation, and Price Earning Ratio (PER) is market price of share devide by earning per share. Increase of EPS and PER is very attractive for investor decision to buy and hold of the share. Food and beverage company is one of several company wich establish and exist during crisis, eventuallly of economic crisis. The formulation of study are: how the effect of EPS to price of share; how the effect of PER to price of share; and how the effect of EPS and PER to price of share simultaneously on food and beverage company whose listed on IDX for the 2015 – 2019 period. And among of 18 company only 9 company who can to be sample with purpose sample method. The research used multiple regression linear for partial and simultant influence both dependend variable to independent variable, and the result shown below; a) The result of this study partially have an effect between EPS to price of share of F&B company on 2015 – 2019 period, where t count (12,332) above t table (2,01669) ; b) Have an effect partially between PER to price of share, where t count (9,455) above t table (2,01669); c) Simultaneously there are an influence between EPS and PER to Price of Share on F&B company on IDX listed for the 2015-2019 period, wichever t count (76,102) above t table (3,21); d) Variant that occur in EPS and PER variables can affect the stock price variable by 61,5 %, while the remaining 38,5 % is influence the other variable.